Electronic Notification : A Comparative Study - Bdaiwi, Hamid; Al-Alaween, Kamal (Journal of Legal Sciences, 2026)
This research addresses the concept of electronic notification, its characteristics, and the electronic means used in its implementation, including what are the means and the conditions for their use. It also clarifies the nature of the judicial paper subject to notification, its characteristics, and the legal validity of electronic notification in terms of the conditions for acquiring such validity and verifying its accuracy. Comparative legislation has varied in adopting electronic notification; some, like Jordanian and French legislation, have embraced it comprehensively and extensively, while others, such as Egyptian and Iraqi legislation, have adopted it in a more limited scope. The researcher concluded with several findings and recommendations, the most important of which are: the significance of utilizing electronic means in judicial notification due to their speed, efficiency, and cost-effectiveness; the necessity of regulating this process through specific legislation aligned with its nature and intended purpose; and the need to provide sufficient safeguards to ensure the provision of accurate and reliable official information and data, guaranteeing the proper use of these means and the successful delivery of the notification document to the intended recipient, "The researchers also recommend that the Iraqi legislator issue a law regulating the provisions of this notification and benefit from the experiences of other countries, especially neighboring ones.